Antibacterial effects of blackberry extract target periodontopathogens. (19th July 2012) - González, O. A.; Escamilla, C.; Danaher, R. J.; Dai, J.; Ebersole, J. L.; Mumper, R. J.; Miller, C. S.
<x xml:space="preserve">Abstract</x> Background and Objective: Antimicrobial agents provide valuable adjunctive therapy for the prevention and the control of oral diseases. Limitations in their prolonged use have stimulated the search for new, naturally occurring agents with more specific activity and fewer adverse effects. Here we sought to determine the antibacterial properties of blackberry extract (BBE) in vitro against oral bacterial commensals and periodontopathogens. Material and Methods: The effects of whole and fractionated BBE on the metabolism of 10 different oral bacteria were evaluated using the colorimetric water‐soluble tetrazolium‐1 assay. The bactericidal effects of whole BBE against Fusobacterium nucleatum were determined by quantitating the numbers of colony‐forming units (CFUs). Cytotoxicity was determined in oral epithelial (OKF6) cells. Results: BBE at 350–1400 μg/mL reduced the metabolic activity of Porphyromonas gingivalis, F. nucleatum and Streptococcus mutans. The reduced metabolic activity observed for F. nucleatum corresponded to a reduction in the numbers of CFUs following exposure to BBE for as little as 1 h, indicative of its bactericidal properties. An anthocyanin‐enriched fraction of BBE reduced the metabolic activity of F. nucleatum, but not of P. gingivalis or S. mutans, suggesting the contribution of species‐specific agents in the whole BBE. Oral epithelial cell viability was not reduced following exposure to whole BBE (2.24–1400 μg/mL) for ≤ 6 h. Conclusion: BBE alters the metabolic activity of oral periodontopathogens while demonstrating a minimal effect on commensals. The specific antibacterial properties of BBE shown in this study, along with its previously demonstrated anti‐inflammatory and antiviral properties, make this natural extract a promising target as an adjunct for prevention and/or complementary therapy of periodontal infections.